Optimalisasi Komunikasi Organisasi Dalam Penguatan Eksistensi Kelembagaan Dewan Energi Nasional - Mandala, Agung; Toni, Ahmad (Jurnal Publisitas, 2024)
Powering the country's energy strategy is the impartial and everlasting National Energy Council. The Energy Law 30 of 2007 constituted the legal basis for the formation of DEN. The seven ministers directly responsible for energy supply, transportation, distribution, and consumption make up DEN, which is led by the President of the Republic of Indonesia and represented by the Vice President of the Republic of Indonesia. Public Relations' "pencils" approach is the focus of this study. This approach seeks to establish positive connections with key stakeholders via the use of publications, events, news, community participation, identity tools, lobbying, and social investment. A descriptive research strategy based on a qualitative paradigm was used in the study process. According to the findings, DEN Public Relations has been trying to solidify its position in the market by using the "pencils" PR technique. In an attempt to fortify institutions, pencils are being used.